Spillovers of banking regulation: The effect of the German bank levy on the lending rates of regional banks and their local competitors - Ulrich Haskamp (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
During the financial crisis numerous European governments decided to rescue domestic banks with public funds to prevent a collapse of the banking system. To internalize the public costs, bank levies have been introduced in many countries. This paper analyzes the German bank levy which was implemented from 2011 till 2014 and its effect on lending rates of regional banks. We examine not only if banks shift the cost of the levy to their customers' lending rates, but also whether there are spillovers to their local competitors. The German savings and cooperative banks are a perfect setting to study such effects as they only operate within well-defined regions, allowing us to identify their local competitors. Additionally, only some of them are subject to the levy due to a tax allowance. Further, with a market share of 42.8% in total, they are relevant. Firstly, we find that a bank that has to pay the bank levy raises its lending rate by about 0.14 percentage points. Secondly, we examine whether the increased lending rates of paying banks spill over to their local competitors. We find this indirect effect to be about one third of the size. Given an average lending rate of 4.96%, these effects are economically significant. Lastly, adverse effects of the levy on paying banks' loan supply growth are absorbed by their competitors to a certain extent. – – Zahlreiche europäische Regierungen haben während der Finanzkrise Banken mit Steuergeldern gerettet, um einen Kollaps des Bankensystems zu verhindern. Um diese Kosten in Zukunft zu internalisieren, wurden in vielen Ländern Bankenabgaben eingeführt. Dieses Papier analysiert die deutsche Bankenabgabe, welche von 2011 bis 2014 in Kraft war, und ihren Einfluss auf die Kreditzinsen von regionalen Banken. Wir untersuchen dabei nicht nur, ob Banken die Kosten der Bankenabgabe auf die Kreditzinsen ihrer Kunden aufschlagen, sondern auch mögliche regionale Effekte auf die Kreditvergabe ihrer lokalen Konkurrenten. Die deutschen Genossenschaftsbanken und Sparkassen eignen sich besonders gut für eine solche Analyse, da sie nur regional tätig sind und wir somit ihre lokalen Konkurrenten identifizieren können. Zudem sind aufgrund ihrer geringen Größe nur einige von ihnen von der Bankenabgabe betroffen. Sie sind aber nichtsdestotrotz relevant für die deutsche Wirtschaft, da sie zusammen auf einen Marktanteil in der Kreditvergabe von 42,8% kommen. Wir finden in unserer empirischen Analyse, dass Banken, die von der Bankenabgabe betroffen sind, ihre Kreditzinsen um 0,14 Prozentpunkte anheben. Des Weiteren ziehen auch ihre lokalen Konkurrenten nach und erhöhen die Zinsen um 0,04 Prozentpunkte. Da die durchschnittlichen Kreditzinsen der Genossenschaftsbanken und Sparkassen in diesem Zeitraum bei nur knapp 5% liegen, sind diese Effekte ökonomisch bedeutsam.
Keywords: E43; G21; G28; R10; 330; bank regulation; bank levy; regional spillover; lending rates